2014
DOI: 10.1002/acr.22370
|View full text |Cite
|
Sign up to set email alerts
|

Electrocardiographic Findings in Systemic Lupus Erythematosus: Data From an International Inception Cohort

Abstract: Objective. To estimate the early prevalence of various electrocardiographic (EKG) abnormalities in patients with

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
43
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 34 publications
2
43
0
Order By: Relevance
“…We and 88% of the patients were females (8). Therefore, the results of these studies are consistent with each other, which is due to the increased incidence of lupus among women at the peak of their childbearing age.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…We and 88% of the patients were females (8). Therefore, the results of these studies are consistent with each other, which is due to the increased incidence of lupus among women at the peak of their childbearing age.…”
Section: Discussionsupporting
confidence: 84%
“…Abnormal repolarization is usually revealed by a prolonged modified QT interval. These ECG abnormalities are associated with an increased risk of cardiac arrhythmias and sudden cardiac death (7,8). The early diagnosis of these abnormalities and electrocardiographic abnormalities may be of prognostic value, playing an important role in determining the prognosis of the disease (8).…”
Section: Introductionmentioning
confidence: 99%
“…26 Although the study of cardiac conduction defects in SLE had been limited primarily to neonatal lupus in association with anti-SSA/Ro antibodies,27 a recent study that evaluated the prevalence of ECG abnormalities in an inception SLE adult cohort found that 31% of patients had non-specific ST-T abnormalities and 15% had a prolonged QTc;7 however, no comparison group was included and 74% of the patients were white and Asian. Our study addressed a gap in identifying the prevalence of these ECG abnormalities in a cohort of patients with SLE of mainly Hispanic and black origins, as well as at different clinical stages of the disease and hence with longer disease duration and a higher mean SLEDAI-2K score as compared with the patients studied by Bourré-Tessier et al 7. More importantly, the fact that in our study over half of the patients with SLE had non-specific ST-T abnormalities as compared with only 17% of the older, more male encompassing RA group is striking and underscores the need for evaluations that detect subclinical cardiovascular involvement in SLE.…”
Section: Discussionmentioning
confidence: 99%
“…Although only explored in one recent study, ECG non-specific ST-T abnormalities were reported in 31% of patients with SLE from an inception cohort; additionally, a prolonged corrected QT-interval (QTc) was noted in 15% of patients 7. However, Bourré-Tessier et al lacked a comparison group and the patients consisted of predominantly whites and Asians with mild disease activity.…”
Section: Introductionmentioning
confidence: 99%
“…Bourre Tessier et al 9 analysed the electrocardiographic abnormalities in 779 patients with SLE, describing nonspecific repolarization changes, without association between QTc duration and specificity or level of anti-Ro/SSA antibodies. However, the included patients were characterized by a short duration of disease (10.5 months), without specifically collected data about the cumulative dose of HCQ and possible electrocardiographic changes.…”
Section: Discussionmentioning
confidence: 99%